Faixas de proteção ambiental do Rio Pitimbu/RN: uma análise como subsídio ao planejamento e ordenamento do território - Silva, Helania Pereira da (2012)
The Environmental Protection area sof Pitimbu river are important tools for planning and territorial land management. The Pitimbu river protection is aided in laws, so much of Federal stamp, as the Brazilian s Forest Code (Law No. 4771/1965), and in State s and City s Resolutions. So, this research begins in the State s Law No. 8426/2003interpretations, for being the most restrictive in the river's margin occupation and management. The objective is to analyze the applicability of the Environmental Protection areas of Pitimbu river, localized at the State of Rio Grande do Norte, considering environmental legislation and how to use this space by the man. Having specific goals for the discussion of the legislation s scope to this river; the identification of the types of soil s covering and evaluation the effectiveness of Law Nº.8426/2003, as protection instrument and land management. The river is characterized by its ecological importance and for feeding the Jiqui pond, an important reservoir that supplies 30% of drinking water to the east, west and south population sof the capital of the State. Pitimbu river is passing by a process of environmental degradation, originating from actions as deforestations of its ciliary forests by intensive agricultural practices; introduction of urban and industrial effluents leading to its contamination; increase of the pluvial drainage; erosion, sedimentation and discharge of urban waste , along with pressure for urban settlements along its banks. Under the methodological point of view is part of theoretical planning and land management research, and from a vision of social and environmental spaces. It was produced a survey map of the soil s covering, with 16 classes. Divided into coverage and disturbed natural covering. Using the 300 meters spatial limits of the Environmental Protection Strip, according to the State Law. The survey highlighted a higher percentage of classes disturbed, indicating man s interference in the balance of that system, as well as the lack of environmental actions. Leading to the degradation of riparian areas, and lack of conservation of water resources. Finally, it was considered that the strips of environmental protection are not effective as the preservation and territorial ordination